2015
DOI: 10.1155/2015/616787
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Neutropenia Induced by Rituximab in a Patient with Lupus Nephritis and Hemolytic Anemia

Abstract: Rituximab is an anti-CD20 monoclonal antibody that has been used to treat several complications of systemic lupus erythematosus (SLE) including nephritis, cerebritis, and hematological disorders. Neutropenia is among the adverse events associated with rituximab; this usually occurs several weeks after therapy. However, early-onset neutropenia has been reported only in a few cases. Herein, we describe a 36-year-old Hispanic SLE woman who developed severe early-onset neutropenia (0.3 × 109/L) after the second we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…Similar to sepsis, each hour of delay in the initiation of effective antibiotics led to an 18 % increase in the 28-day mortality risk [20]. In addition, we consider that rituximab may induce earlyonset neutropenia in case 3 [21]. The characteristics of Although UTI was the leading cause of bacteremia, respiratory tract infections were the primary cause of infections requiring ICU admission (accounted for 54 %) in KTR [22].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to sepsis, each hour of delay in the initiation of effective antibiotics led to an 18 % increase in the 28-day mortality risk [20]. In addition, we consider that rituximab may induce earlyonset neutropenia in case 3 [21]. The characteristics of Although UTI was the leading cause of bacteremia, respiratory tract infections were the primary cause of infections requiring ICU admission (accounted for 54 %) in KTR [22].…”
Section: Discussionmentioning
confidence: 99%
“…Two forms of rituximab‐induced neutropenia have been described: early‐onset neutropenia (EON) occurs within 4 weeks of treatment initiation, while late‐onset neutropenia (LON) occurs at least 4 weeks after termination of the drug . LON has been described more frequently than EON, which is uncommonly reported . We present a unique case of EON after rituximab in a patient with refractory BP.…”
Section: Reported Cases Of Early‐onset Neutropenia After Rituximabmentioning
confidence: 96%
“…Although rituximab possesses an excellent safety profile, neutropenia is a known idiosyncratic adverse effect (AE) of the drug . Two forms of rituximab‐induced neutropenia have been described: early‐onset neutropenia (EON) occurs within 4 weeks of treatment initiation, while late‐onset neutropenia (LON) occurs at least 4 weeks after termination of the drug . LON has been described more frequently than EON, which is uncommonly reported .…”
Section: Reported Cases Of Early‐onset Neutropenia After Rituximabmentioning
confidence: 99%
See 1 more Smart Citation
“…One case of LON has been reported in an NMO patient (Plate et al, 2014). In contrast, early-onset rituximab-induced neutropenia has been described in SLE (Gottenberg et al, 2005; Enríquez et al, 2007), and early-onset agranulocytosis has also been reported (Arroyo-Ávila et al, 2015) but early-onset agranulocytosis has not yet been reported in NMO. We reported two cases of early on-set rituximab-induced agranulocytosis in NMO.…”
Section: Introductionmentioning
confidence: 99%